Response of Skin-Derived and Metastatic Human Malignant Melanoma Cell Lines to Thymoquinone and Thymoquinone-Loaded Liposomes - Patrycja Kłos; Magdalena Perużyńska; Magdalena Baśkiewicz-Hałasa; Paulina Skupin-Mrugalska; Małgorzata Majcher; Magdalena Sawczuk; Bartosz Szostak; Marek Droździk; Bogusław Machaliński; Dariusz Chlubek (Pharmaceutics, 2022)
Thymoquinone has been proved to be effective against neoplasms, including skin cancer. Its high lipophilicity, however, may limit its potential use as a drug. Melanoma remains the deadliest of all skin cancers worldwide, due to its high heterogeneity, depending on the stage of the disease. Our goal was to compare the anti-cancer activity of free thymoquinone and thymoquinone-loaded liposomes on two melanoma cell lines that originated from different stages of this cancer: skin-derived A375 and metastatic WM9. We evaluated the proapoptotic effects of free thymoquinone by flow cytometry and Western blot, and its mitotoxicity by means of JC-1 assay. Additionally, we compared the cytotoxicity of free thymoquinone and thymoquinone in liposomes by WST-1 assay. Our results revealed a higher antiproliferative effect of TQ in WM9 cells, whereas its higher proapoptotic activity was observed in the A375 cell line. Moreover, the thymoquinone-loaded liposome was proved to exert stronger cytotoxic effect on both cell lines studied than free thymoquinone. Differences in the response of melanoma cells derived from different stages of the disease to thymoquinone, as well as their different responses to free and carrier-delivered thymoquinone, are essential for the development of new anti-melanoma therapies. However, further research is required to fully understand them.